Między starym a nowym: źródła wiedzy licealistów o polityce w procesie socjalizacji - Jakubowski, Jakub (Studia Edukacyjne, 2021)
The process of political socialization takes place on many levels and depends on various factors, such as family, peer group or school. The basic catalog of them includes the media as well. The main ob[1]jective of the article is to diagnose their role in the process of social adjustment in the area of politics of high school youth from the region of Wielkopolska. The surveys conducted among high school students helped examine a number of factors: sources of knowledge about politics, media formats on the Internet as well as the most important actors playing the role of opinion leaders in the process of political socialization of young people. The study proved that young people display features of media use characteristic of “traditional” mass communication tools (such as television), but also a tendency to use new forms of media, characteristic of “generation Z”. At the same time, significant differences in this respect were observed on the grounds of gender and the declared approach to the religion by young people from Wielkopolska region.